2020
DOI: 10.1002/mbo3.1029
|View full text |Cite
|
Sign up to set email alerts
|

A membrane‐bound [NiFe]‐hydrogenase large subunit precursor whose C‐terminal extension is not essential for cofactor incorporation but guarantees optimal maturation

Abstract: [NiFe]‐hydrogenases catalyze the reversible conversion of molecular hydrogen into protons end electrons. This reaction takes place at a NiFe(CN)2(CO) cofactor located in the large subunit of the bipartite hydrogenase module. The corresponding apo‐protein carries usually a C‐terminal extension that is cleaved off by a specific endopeptidase as soon as the cofactor insertion has been accomplished by the maturation machinery. This process triggers complex formation with the small, electron‐transferring subunit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 50 publications
(99 reference statements)
1
10
0
Order By: Relevance
“…Both RH and the isolated catalytic HoxC are fully equipped with an intact NiFe(CN) 2 (CO) cofactor when purified from their original host R. eutropha [14]. Thus, a C-terminal extension is not required for either the subunit assembly or for the interaction with the Hyp apparatus [58]. Our data on the heterologously produced RH stop suggest that HoxBC assembly is not triggered by the presence of the [NiFe] cofactor.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Both RH and the isolated catalytic HoxC are fully equipped with an intact NiFe(CN) 2 (CO) cofactor when purified from their original host R. eutropha [14]. Thus, a C-terminal extension is not required for either the subunit assembly or for the interaction with the Hyp apparatus [58]. Our data on the heterologously produced RH stop suggest that HoxBC assembly is not triggered by the presence of the [NiFe] cofactor.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, the mature HoxB subunit seems to form a complex with the [NiFe] cofactor-free HoxC subunit, revealing a partially mature RH. These data are quite surprising as it was previously believed that the RH possess an intrinsic proofreading mechanism preventing the complex formation of premature subunits [58]. The RH from R. eutropha belongs to the [NiFe]-hydrogenases lacking the C-terminal peptide extension of the large subunit.…”
Section: Discussionmentioning
confidence: 92%
“…Given that in S. enterica a maturation protease was found to retain the ability to recognize and bind to a large subunit completely lacking the maturation peptide [ 34 ], perhaps it should be considered that the maturation protease has a role in hydrogenase biosynthesis beyond the simple cleavage of the C-terminal extension. This could certainly be tested in the C. necator system [ 40 ] by deleting the gene encoding the processing protease (HoxM [ 41 ]) in the stain already lacking the hydrogenase assembly peptide and observing any changes to hydrogenase activity.…”
Section: Full-textmentioning
confidence: 99%
“…Protelolytic processing is not required for all [NiFe]-hydrogenases, such as examples of the H 2 -sensing, Ech-and CODH-linked hydrogenases [36][37][38][39]. Indeed, recent genetic engineering work showed that removal of the C-terminal assembly peptide from the membrane bound hydrogenase (MBH) in Cupriavidus necator (Ralstonia eutropha) did not disrupt cofactor insertion and resulted in no loss of hydrogenase-specific activity [40]. Given that in S. enterica a maturation protease was found to retain the ability to recognize and bind to a large subunit completely lacking the maturation peptide [34], perhaps it should be considered that the maturation protease has a role in hydrogenase biosynthesis beyond the simple cleavage of the C-terminal extension.…”
mentioning
confidence: 99%
“…15 Cleavage of a C-terminal extended domain induces proper folding, and binding to the small, [FeS]-cluster containing subunit gives the fully assembled hydrogenase. 16,17 The complexity of this pathway coupled with the still-unknown metabolic precursor of the CO ligand on Fe in the standard enzymes and, until recently, a lack of effective in vivo activity screens have hindered efforts to evolve hydrogenases in order to enhance specific activity traits. 18,19 On the other hand, the artificial enzyme scaffold, rubredoxin, is encoded on a pET21a(+) plasmid containing the lac promoter.…”
mentioning
confidence: 99%